Analysis of Human Resources Competence in the Digital Era As Staff Qualifications and Education in Quality Improvement at Kartika Husada Hospital in 2023 - Saputri, Agnes Ratna; Manik, Maggie Juntiven (Yayasan Gema Bina Nusantara, 2024)
The purpose of this study was to analyze the level of human resource (HR) competency in supporting hospital management information systems, and to understand the qualifications and impacts of the digital era on HR performance, including management strategies for facing structural transformation and work culture in the digital industry. This study employs a qualitative, descriptive exploratory approach to investigate the correlation between job satisfaction, hospital service quality, and HR competency. This method uses semi-structured interviews and open-ended questionnaires to collect data from human resources at the hospital, as well as from ten families of patients who have completed treatment. This study also collected secondary data through documents such as company profiles and websites. The researcher acted as a